Effectiveness RADEC based multiliteracies approach on logical and reflective thinking skills of elementary school students - Wibowo, Sigit; Mudiono, Alif; Khoiriya, Rika Mellyaning; Faiza, Afidatun; Ardhiansyah, Ikhwan; Azizah, Maulidatul (Universitas Kanjuruhan Malang, 2026)
Logical and reflective thinking are key components of higher-order thinking in 21st-century education, yet many elementary students’ abilities remain underdeveloped due to teacher-centered instruction. This study investigates the effectiveness of a RADEC-based multiliteracy approach in enhancing these skills among fifth-grade students. Using a quasi-experimental pretest–posttest control group design, 45 students in Malang, Indonesia (22 experimental; 23 control) participated in the study. Data were collected through validated logical and reflective thinking tests, supported by observations and interviews. Results showed significant differences between groups. The experimental group outperformed the control group in logical thinking (M = 75.00 vs. 47.83; p < .001) and reflective thinking (M = 81.41 vs. 40.65; p < .001). The findings suggest that the structured RADEC stages integrated with multiliteracy principles effectively foster systematic reasoning and metacognitive reflection, demonstrating strong pedagogical potential for promoting higher-order thinking in elementary education.